PELATIHAN PEMBELAJARAN INTERAKTIF DENGAN MEDIA “KARTU SHAH” UNTUK MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI YAYASAN AT-TAQWA VIII TARUMAJAYA, BEKASI - Fatwa Arifah; Muhammad Kamal; Ahmad Marzuq; Hendrawanto; Puti Zulharby (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
Abstract Improving teachers' professional competence is one of the crucial factors in supporting learning success. At the At-Taqwa VIII Foundation, Karang Tengah, Bekasi, the results of the situation analysis showed that 13.8% of teachers had not participated in professionalism training for a long time, and only 24.1% of teachers had received training in the past year. This community service activity aims to train teachers at the At-Taqwa VIII Foundation in applying